Evaluation of the room smoke filling time for fire plumes: Influence of the room geometry. (23rd June 2020) - Haouari‐Harrak, S.; Mehaddi, R.; Boulet, P.; Koutaiba, E.M.
Summary: The article examines numerically and theoretically the effects of room aspect ratio on the fire smoke filling process. It aims to evaluate the two‐zone models used in fire safety engineering to predict the smoke filling times. Using Fire Dynamics Simulator, numerical simulations are performed and compared to a simplified zone model. The results show that the two‐zone model overestimates the smoke filling time in the case of a compartment with a large surface area. To improve the predictions of two‐zone models, simple correlations are established for the duration of the phenomena occurring before the formation of a two‐layer stratification in a fire compartment. These new correlations allow the zone model to be significantly improved.